Implementasi Kewenangan Badan Permusyawaratan Desa Mengusulkan Pemberhentian Kepala Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 - Jumari Jumari; Jamri Jamri; Kms. Novyar Satriawan Fikri (MAN 4 Kota Pekanbaru, 2026)
This study examines the implementation of the Village Consultative Body’s (BPD) authority to propose the dismissal of the Village Head in Nyiur Permai Village, Indragiri Hilir Regency, based on Law Number 6 of 2014 concerning Villages. It also analyzes factors affecting the exercise of this authority and its compliance with legal provisions. This research was motivated by the BPD’s decision in a village deliberation on May 17, 2025, to propose the dismissal of the Village Head due to the unresolved 2024 Budget Surplus (SiLPA) and to suggest the appointment of an Acting Village Head (PLT). Using empirical legal research with a sociological approach, data were collected through interviews with BPD officials and the Village Head, supported by legal literature. The findings show that the BPD’s action represents a form of governance oversight. However, its implementation is influenced by financial transparency, public pressure, political dynamics, and limited understanding of legal authority. The proposal to appoint a PLT before an official dismissal decision indicates non-compliance with the principle of legality.